Nitrogen distribution in apple orchard soil profile under fertilization with different water and fertilizer coupling techniques - Zhao, Zuoping; Yan, Sha; Hu, Siyu; Qu, Kaijing; Tong, Yan’an (International Journal of Agricultural and Biological Engineering, 2022)
Optimization of water and fertilizer coupling management approaches could not only increase apple yield and quality, but also reduce the potential negative impacts of such management activities on the environment. The aim of the present study was to determine the optimal water-nitrogen (WN) coupling management strategy in an apple orchard in the Weibei Dryland, Shaanxi Province, China, under limited irrigation. A randomized complete block design was adopted to test the effects of three drip irrigation levels (W1, 300 m3/hm2; W2, 600 m3/hm2; W3, 900 m3/hm2) and four N application levels (N0, 0 kg/hm2; N1, 200 kg/hm2; N2, 400 kg/hm2; and N3, 600 kg/hm2) on N distribution in the 0-100 cm soil profile. Apple yield and economic benefits under different treatments were also evaluated over a three-year period (2012-2014). Compared with the N0W1 treatment, soil N contents were higher and exhibited distinct trends in the soil profile under other treatments. Overall, total N contents exhibited a downward trend from the surface to the subsurface layers (0.11-2.34 g/kg); however, the total N contents of the lower soil layer increased with an increase in irrigation amount. NO3-N contents were the lowest in the 40- 60 cm soil layer and then increased with an increase in soil depth. The highest NO3-N contents of different soil layers were observed under the N3W3 treatment, ranging from 124.7 mg/kg (0-20 cm) to 90.9 mg/kg (80-100 cm). NH4+-N contents were low (<10 mg/kg), mainly accumulating in the surface layer and decreasing toward the deeper layers>20 cm. Different water-N coupling treatments also increased apple yield by 7.30%-41.62% when compared with the N0W1 treatment. The highest apple yield (three-year mean: 41.01 t/hm2) was observed under the N2W2 treatment, with an output value of 237 900 RMB yuan/hm2 and a net income of 232 000 RMB yuan/hm2. Considering fruit yield, partial productivity of N fertilizer, and economic and environmental benefits, the N2W2 treatment is the optimal water-N fertilizer coupling drip irrigation scheme for apple production in the study area and other similar dryland areas. Keywords: apple orchard, water-nitrogen coupling, nitrogen fertilization, soil profile, yield DOI: 10.25165/j.ijabe.20221505.7257 Citation: Zhao Z P, Yan S, Hu S Y, Qu K J, Tong Y A. Nitrogen distribution in apple orchard soil profile under fertilization with different water and fertilizer coupling techniques. Int J Agric & Biol Eng, 2022; 15(5): 146–154.